A scientometrics review of nozzle wear in abrasive waterjet machining - Nuraini, Lusi; Catrawedarma, I Gusti Ngurah Bagus; Gebremariam, Mebrahitom; Saptaji, Kushendarsyah; Mohd Azmir, Mohd Azhari (Springer, 2025)
One of the most common issues with the abrasive waterjet machining (AWJM) process is nozzle degradation, which occurs when abrasive particles continuously erode the nozzle wall. The cutting performance will be impacted as a result of the worn nozzle. Thus, this paper presents a scientometric analysis of research papers on nozzle wear, with key findings including the leading contributing countries, most common publication types, and leading publishers. Noting a notable rise in publications, it highlights well-liked areas and tracks the development of nozzle wear research over time and identifies trends in keywords that point to recurrent themes in the field. 103 articles were retrieved from Scopus electronic database and they span between 1984 and 2024. Bibliometric software VOSviewer and Biblioshiny were used to create a graphical depiction using bibliometric co-citations and collaborations of the relationships between the authors, nations, affiliations and keywords. The most productive authors in the field of nozzle wear in AWJM were discovered to be American and Indian. This paper aims to support researchers, whether experienced or novice, who have a strong interest in nozzle wear-related studies in forming research partnerships or obtaining funding from corporations, governments, or private sources.